REDESAIN PILAR JEMBATAN AKIBAT POSISI PILE CAP YANG TIDAK MEMENUHI PERSYARATAN - Indianto, Andi; Rizal, Shafaa Yosvi Rahmathullah (Construction and Material Journal, 2024)
This research aims to find effective design alternatives for bridge pillars whose position must be shifted away from the existing gas pipe, which was originally 2m to more than 3m. This pillar shift is intended so that the position of the pile cap pillar meets the requirements set by the Minister of Mining and Energy number 300.k/38/m.pe/1997 regarding work safety in oil and gas distribution pipes. To get an effective design, several forms of pillar design were carried out without having to change the span of the bridge's upper structure. An effective design form is tipe 1 (pile cap tipe) bridge pillars rather than tipe 2 (single column), because tipe 1 pillars have an implementation time of 42 days while tipe 2 is 94 days, so the implementation of tipe 1 pillars is 52 days faster than the pillars. tipe 2. The results of the structural analysis, tipe 1 pillar (pile cap tipe) obtained pile cap reinforcement which functions as a pier head of D32-80 in the transverse direction and D32-150 in the longitudinal direction, with a foundation that directly functions as a pillar using concrete spun pile D800mm as many as 60 pieces which are stuck into the ground to a depth of 24 m.